Examining the effects of psychological resilience and wellbeing on perceived stress and depressive symptoms among undergraduate nursing interns: testing a moderated mediation model - Yan, Miaomiao; Zhang, Lijuan; Qin, Dan; Zhou, Zhongtao; Wu, Yigao; Hou, Nuoyu; Tao, Xiubin (Frontiers in Public Health, 2024)
BackgroundPerceived stress is recognized as a significant risk factor for depressive symptoms, while psychological resilience and wellbeing are considered crucial protective factors. However, the intricate relationships among these variables in undergraduate nursing interns remain largely unexplored. This study aims to investigate the mediating role of psychological resilience in the relationship between perceived stress and depressive symptoms, as well as the moderating influence of wellbeing on this mediation.MethodsFrom March 1 to 31, 2024, a cluster sampling survey was conducted to examine senior nursing undergraduates from a medical college in Anhui Province who were engaged in clinical practice at various hospitals. The surveyed hospitals were all Grade III, and Class A teaching institutions situated in Anhui, Jiangsu, Zhejiang, Shanghai, and other provinces. According to the Lewinsohn behavioral theory of depression, the study measured perceived stress, depressive symptoms, wellbeing, and psychological resilience using the Chinese Perceived Stress Scale (CPSS), Patient Health Questionnaire 9 (PHQ-9), Oxford Happiness Questionnaire (OHQ), and the Chinese version of the 10-item Connor-Davidson Resilience Scale (CD-RISC-10). The PROCESS v4.0 macro was utilized to evaluate the mediating role of psychological resilience and the moderating role of wellbeing.ResultsA total of 299 valid samples were included. Perceived stress, depressive symptoms, psychological resilience, and wellbeing were significantly correlated. Psychological resilience partially mediated the relationship between perceived stress and depressive symptoms [indirect effect = 0.111, 95% Boot CI (0.065, 0.162)]. Wellbeing also moderated the relationship between psychological resilience and depressive symptoms [B = 0.007, 95% Boot CI (0.003, 0.011)].ConclusionThe mental health of undergraduate nursing interns warrants attention. To reduce perceived stress and depressive symptoms, interventions should focus on enhancing psychological resilience and wellbeing among these interns.